The Japanese Emperor between the 1889 and 1946 Constitutions: – A Comparative Study - Mohammed Ali, Afrah (Al-Adab Journal, 2019)
The study of the Japanese Emperor between the 1889 and 1946 constitutions is considered important, as the role of the Emperor has been significantly affected by these two constitutions. This effect is reflected in the Japanese History. This study shows the status of the emperor and his authority under the most notable two constitutions in the history of modern and current Japan. The 1889 Meiji constitution, was formulated and set up to strengthen the authority of the emperor and restore the actual stripped authority to him for more than a millennium. The 1946 constitution was made by allied and American forces, which occupied Japan after the latter lost the Second World War, after it became an imperialistic occupying nation, whose danger was extending on the regional and international fields. This study shows how the vast authorities of the Japanese Emperor were abolished and the Meiji constitution was revoked and replaced by the occupation constitution for 1946.